Risk Factors Contributing to Short Stature in Full-Term Children Born Small for Gestational Age (SGA) - Abbas Ali Khan, Muhmamad Qasim Khan, Warda Gul, Waqas Alam, Aimen Khan (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Children born small for gestational age (SGA) face an increased risk of impaired growth despite being full-term. Identifying the determinants of short stature in this group is essential for guiding early interventions. Objective: To determine the risk factors associated with short stature among full-term children born SGA. Methods: A cross-sectional study was conducted at Mardan Medical Complex, Mardan, from January 2022 to January 2023. A total of 82 children aged 2–10 years, born full-term SGA, were enrolled. Demographic, parental, perinatal, nutritional, and environmental factors were recorded through structured questionnaires. Anthropometric measurements were taken, and growth was assessed using WHO growth standards. Short stature was defined as a height-for-age Z-score < –2 SD. Statistical analysis was performed using SPSS version 26, with p <0.05 considered significant. Results: The prevalence of short stature was 34.1% (28/82). Low birth weight (<2.5 kg), maternal short stature, low socioeconomic status, shorter breastfeeding duration, and recurrent infections showed significant associations with short stature (p <0.05). Gender, residence, and exposure to passive smoking were not significantly related. Conclusion: Full-term children born SGA remain at high risk of short stature, particularly when compounded by poor perinatal conditions, parental short stature, socioeconomic disadvantage, and inadequate nutrition. Early screening, parental education, and community-based nutritional support are critical for reducing stunting in this vulnerable group. Keywords: Short stature, Small for gestational age, Birth weight, Child growth, Risk factors, Nutritional status